Islam in History - Kokab Arif (International Institute of Islamic Thought, 1993)
Malek Bennabi (1903-73) was an Algerian scholar who received his education in Algiers and Paris. An engineer by training, his concern about the ummah 's decadence led him to analyze the causes of this decay and to provide solutions. The result of his analysis is this book. Originally written in French in 1943 W1der the title Vocation de /'Islam, it was not published until I 954, in order to coincide with the Algerian revolution. At the outset, he defines history by saying that history is a sociology, that is, the study of the conditions of development of a social group, defined not as much by its ethical or political factors as by the complex of ethical, aesthetical, and teclmical affinities corresponding to the air or space of this civilization. On the other hand this social group is not isolated, and its evolution is conditioned by certain connections with the human ensemble. From this point of view, history is a metaphysics, since its perspective, extending beyond the domain of historical causality, embraces the phenomena in their finality. (p. 6) Using this framework, he develops a cyclical concept of civilization and attributes its origin to Ibn Khaldiin. He argues that the phenomenon of "civilization" and "decadence" should not be studied in isolation. This is especially true in the case of the Muslim world, which is in need of clear ideas for its renaissance and should not be isolating the two. Using a sociological base, he focuses on the behavior of the individual in Muslim society. He believes that the decadence of the Muslim ummah is the result of combination of historical and psychological factors. The first turning point came when the democratic caliphate became a dynasty. The second, which was psychological, was the fall of the al Muwahhid dynasty in Spain to the forces of Christendom in the thirteenth century CE. lltls process gave birth to what Bennabi termed the "post-al Muwabhid man" who is the typical representative of the contemporary ummah's behavior, temperament, characteristics, and psychology. While discussing the efforts to improve this situation, he focuses on the ummah's various refonnist and modernist movements. In his view, the reformist movements did not try to .give the post-al Muwabhid ...